2018
DOI: 10.1007/s13187-018-1364-2
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Patient Identification and Narrative Transportation on Intentions to Participate in Cancer Research

Abstract: Cancer decision-making interventions commonly utilize narratives as a persuasive strategy to increase identification with the message source, promote involvement with the topic, and elicit greater willingness to adopt recommended behaviors. However, there is little empirical research examining the mechanisms underlying the effectiveness of this strategy in the context of cancer research participation. Data for the current manuscript were collected as part of a larger study conducted with cancer patients (N = 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Qualitative feedback from patients and caregivers about the website was overwhelmingly positive. Consistent with empirical evidence exploring the positive effect of narratives on health attitudes [26], qualitative data revealed that inclusion of personal narratives (e.g., from cancer survivors, CCT participants) enhanced perceptions of credibility and positively influenced perceptions of information effectiveness among participants. Testimonials enhanced the salience of messages about CCTs among participants and increased their attention to the website.…”
Section: Discussionsupporting
confidence: 68%
“…Qualitative feedback from patients and caregivers about the website was overwhelmingly positive. Consistent with empirical evidence exploring the positive effect of narratives on health attitudes [26], qualitative data revealed that inclusion of personal narratives (e.g., from cancer survivors, CCT participants) enhanced perceptions of credibility and positively influenced perceptions of information effectiveness among participants. Testimonials enhanced the salience of messages about CCTs among participants and increased their attention to the website.…”
Section: Discussionsupporting
confidence: 68%
“…First person storytelling (FPS) from previous patients who have faced or overcome reallife health challenges has the potential to engage patients in different ways than traditional didactic education. Multiple theories, including Narrative Communication Theory [26,[53][54][55], Exemplification Theory [39] and Social Cognitive Theory [56,57] illustrate how FPS may influence decision-making and action. Narrative Communication Theory posits that stories are effective because they transport the audience, [26,[53][54][55] allow the viewer to identify with the storyteller, [58,59] and perceive the story to be real and authentic [60,61].…”
Section: Discussionmentioning
confidence: 99%
“…However, this result may not be surprising for PSA communications in terms of activating empathy potential through character involvement. Albeit the PSA activity, through which the viewers are evoked to a relational experience over character engagement, has been suggested in many studies (Igartua, 2010;Moyer-Gusé, 2008;Neil et al, 2019), the current paper could be deemed considerable in terms of associating character identification with altruistic behaviors and donation intentions.…”
Section: Discussionmentioning
confidence: 97%